Essential words for the GRE - Geer, Philip (Wireless, Barron's, 2016)
An extensive working vocabulary is a prerequisite for test-taking success on the Graduate Record Exam. This book presents 800 graduate-level words with definitions that frequently appear on the exam. Words are used in different contexts to familiarize test takers with their many variations. The book's additional features include a pre-test that helps to diagnose weaknesses, a lengthy word list with extensive practice exercises, and a chapter that discusses and analyzes essential word roots. The book concludes with a post-test to assess progress. Answers are provided for all exercises and for all questions in the pre- and post-test.
Introduction: mastering advanced vocabulary for the GRE -- Pretest -- Suggested study plans -- 300 high-frequency GRE words -- Essential words for the GRE -- Review: 300 high-frequency GRE words -- Review: essential words for the GRE -- 300 high-frequency word roots -- Common suffixes -- Posttest -- Answer keys essential words for the GRE -- Root roundup -- Root roundup review.
Includes index.
CSE
Keywords: Graduate Record Examination -- Study guides; English language -- Glossaries, vocabularies, etc; Vocabulary -- Problems, exercises, etc; English language; Graduate Record Examination; Vocabulary; Glossaries, vocabularies, etc; Problems and exercises; Study guides